Konsep Pemikiran Ibnu Rusyd Dan Relevansinya Terhadap Perkembangan Pendidikan Agama Islam Di Era Revolusi Industri 4.0 - Jaelani, Juhri; Nurlatifah, Nurlatifah; Kusnawan, Kusnawan (PT. Student RIhlah Indonesia, 2025)
In the midst of the enjoyment of technological developments that are all digitalized and automated today, a clear, coherent and systematic mindset is needed. One of them can be found in the thought of Ibn Rushd. This research aims to develop the role of Islamic religious education in the era of the industrial revolution 4.0 in the perspective of Ibn Rushd's thought. This research uses a literature study approach (library research) with the research method using content analysis, namely by analyzing, examining and observing the thoughts of Ibn Rushd and their relevance to Islamic religious education in the era of the industrial revolution 4.0. The results of the study show that explicitly the thought of Ibn Rushd rests on a rationality that is reason or ratio that is able to find divine truth. Ibn Rushd's thinking related to education is theoretical and practical and in its implementation is adjusted to the learning model. Ibn Rushd's thought has relevance to Islamic religious education in the era of the industrial revolution 4.0, it can be seen from the object of his philosophical study of the development of science both exact and metaphysics which has no limit in finding a truth.